2008
DOI: 10.1093/brain/awm324
|View full text |Cite
|
Sign up to set email alerts
|

Is the synchronization between pallidal and muscle activity in primary dystonia due to peripheral afferance or a motor drive?

Abstract: The pathophysiological mechanisms of primary dystonia have largely remained obscure. Yet there is one undeniable observation: lesioning or high-frequency stimulation of the internal segment of the globus pallidus (GP) ameliorates dystonic symptoms. The latter observation implicates abnormal pallidal activity in the genesis of primary dystonia. Recently, excessive oscillatory pallidal activity in the 3-10 Hz frequency range, synchronized with dystonic EMG, has been related to the occurrence of involuntary muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 47 publications
4
68
0
2
Order By: Relevance
“…However, to avoid major confounds induced by abnormal hand movements [shown to induce ␥ activity in generalized dystonia patients, see the study by Liu et al (2008)], we have only included patients with normal hand motor function in our study. It also has to be noted that abnormal muscle activity has been related to increased low-frequency activity (4 -10 Hz) in dystonia patients, and ␥ band activity is usually not found in the resting state pallidal LFP activity (Liu et al, 2008;Sharott et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, to avoid major confounds induced by abnormal hand movements [shown to induce ␥ activity in generalized dystonia patients, see the study by Liu et al (2008)], we have only included patients with normal hand motor function in our study. It also has to be noted that abnormal muscle activity has been related to increased low-frequency activity (4 -10 Hz) in dystonia patients, and ␥ band activity is usually not found in the resting state pallidal LFP activity (Liu et al, 2008;Sharott et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The strength of coherence between EEG and PPNR LFP was approximately 0.1, similar to previous studies of coherences between EEG and STN or GPi LFP. 24,25 Because PPNR coherence with the cortex was found only in the ON state, dopaminergic medications promoted the interactions between the cortex and the PPNR in patients with PD. This is consistent with findings that dopaminergic medications restore the deficient activation of SMA and related motor circuits in PD.…”
Section: Event-related Desynchronization and Synchronizationmentioning
confidence: 99%
“…In A, C, and E, coherence in the theta frequency range (6-10 Hz) was present intermittently from the start to the end of the epoch and diminished for approximately 0.6 seconds before movement onset. Coherence in the beta frequency range (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) was present during the premovement period from approximately Ϫ2.5 to 0 seconds and was most conspicuous in the ipsilateral sensorimotor region (A to D) during ipsilateral ankle movements (C and D). In G and I, coherence in the beta frequency range (15-25 Hz) was present before movement onset.…”
Section: Event-related Desynchronization and Synchronizationmentioning
confidence: 99%
“…Low oscillatory activity was recorded in the GPi of dystonic patients (126). This activity was found to be correlated with dystonic EMG (112,114,127) and single unit neuronal activity (112,128). The conclusion was that the frequency of synchronization in the basal ganglia is a critical problem in dystonia, as in other movement disorders (129).…”
Section: Or Cerebellum (93)mentioning
confidence: 94%
“…They revealed interesting but contradictory data. A trend for low firing rate with a bursty pattern and oscillations was reported in the internal pallidum (112)(113)(114)(115)(116) and subthalamic nucleus (117). However, the role of anaesthesia was debated because some authors found no difference between dystonic and PD patients (118,119).…”
Section: Or Cerebellum (93)mentioning
confidence: 99%